Pengaruh Electronic Word Of Mouth Dan Beauty Vlogger Terhadap Minat Beli Dengan Brand Image Sebagai Variabel Intervening (Studi Kasus pada Mahasiswa Universitas Islam Malang Angkatan 2020) - Argadia, Oka; Hidayati, Nur; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The research aims to determine and analyze the influence of electronic word of mouth, beauty vloggers affects purchase intention with brand image in the role of intervening variable. The population of this research is students of the Islamic University of Malang Class of 2020. This research used a non-probability sampling strategy, namely purposive sampling so that 95 respondents can be determined. One way to analyze data is to use quantitative descriptive methods. The research used a quantitative approach with analysis through the use of SmartPLS data processing. The findings from this research are that electronic word of mouth and beauty vloggers have a significant effect on brand image, brand image has a significant effect on purchase intention, electronic word of mouth and beauty vloggers have a significant effect on purchase intention. Electronic word of mouth has a significant effect on purchase intention through brand image as an intervening variable, and beauty vlogger has a significant effect on purchase intention through brand image as an intervening variable. Keywords : Electronic Word of Mouth, Beauty Vlogger, Brand Image, Purchase Intention.